Sociodemographic and health predictors of concern about COVID-19 infection in Cuban patients with type 2 diabetes mellitus - Caycho Rodríguez, Tomás (2022)
Introduction: Concern about becoming infected is a particularly relevant psychological aspect in the context of a pandemic, as it is associated with social reactions and behavioral changes. Objectives: The present study sought to determine some sociodemographic and health factors associated with concern about COVID-19 infection in Cuban patients with type 2 diabetes mellitus. Methods: 203 patients with type 2 diabetes mellitus, who attended nine primary care areas of four Cuban provinces belonging to different regions of the country (65.52% female, mean age 57.5, SD=19.2), selected through non-probabilistic sampling, participated in the study. A sociodemographic questionnaire, the COVID-19 contagion concern scale (PRE-COVID-19) and an evaluation of blood glucose level were applied. Bivariate associations were examined with a series of analyses of variance (ANOVA). Adjusted (multiple) regression with all predictors running simultaneously was also used. Results: Bivariate analyses showed that age, sex, education, occupation, having comorbidities, and having a family member or friend who had COVID-19 were significantly related to COVID-19 contagion concern. However, when all variables were included simultaneously, only age, technical education, having comorbidities, and having a friend or family member who had COVID-19 remained significant predictors of concern about COVID-19 infection. Conclusions: Male patients, with a technical level of education, with comorbidities and those who had infected family members or friends presented greater concern for the contagion of COVID-19. The public health policies should develop strategies to assess the mental health of people belonging to vulnerable groups and provide interventions to promote mental health in those who show concern about infection.